Differential access to facilities for medical termination of pregnancy and delivery in India: A secondary analysis - Shantanu Sharma; Ajit Kumar Jaiswal; Rajesh Kumar Singh; Paramhans Kumar; Sunil Mehra (Elsevier, 2021)
Introduction: Emerging evidence suggests a difference in access to facilities for medical termination of pregnancy (MTP) and delivery among women in different regions of the country. However, we lack assessments at a large scale across all geographies. Our study aims to describe the percent contribution of private and public sectors in institutional deliveries and MTP in India. Methods: A secondary data analysis using the Health Management Information System statistics was performed. We obtained selective data regarding the total number of MTP and deliveries conducted at public and private institutions. The standard reports of the period between April 2018 and March 2019 were analyzed. The states (n = 29) and union territories (n = 7) were dichotomized into regions, namely north, south, east, west, north-east, and central. Results: A large part of women underwent deliveries and abortions in the private sector in the southern and western states of India like Kerala, Tamil Nadu, Andhra Pradesh, Goa, and Maharashtra. Women in most of the northern states opted for public facilities for deliveries as well as abortions, except Punjab and Haryana. On the contrary, states like Bihar, Nagaland, and Union territories like Delhi and Dadra and Nager Haveli had a high percentage of abortions in the private sector and deliveries in public health facilities. Conclusion: This differential access highlights the need to assess the underlying factors for immediate actions by the policy-makers. Ensuring safe and good quality delivery and abortion services is the means to assure the sexual and reproductive health rights of women by the government.